Idarubicin‐loaded beads for chemoembolisation of hepatocellular carcinoma: results of the IDASPHERE phase I trial. Issue 11 (16th April 2014) - Boulin, M.; Hillon, P.; Cercueil, J. P.; Bonnetain, F.; Dabakuyo, S.; Minello, A.; Jouve, J. L.; Lepage, C.; Bardou, M.; Wendremaire, M.; Guerard, P.; Denys, A.; et al.
Summary Background A phase I dose‐escalation trial of transarterial chemoembolisation (TACE) with idarubicin‐loaded beads was performed in cirrhotic patients with hepatocellular carcinoma (HCC). Aim To estimate the maximum‐tolerated dose (MTD) and to assess safety, efficacy, pharmacokinetics and quality of life. Methods Patients received a single TACE session with injection of 2 mL drug‐eluting beads (DEBs; DC Bead 300–500 μm) loaded with idarubicin. The idarubicin dose was escalated according to a modified continuous reassessment method. MTD was defined as the dose level closest to that causing dose‐limiting toxicity (DLT) in 20% of patients. Results Twenty‐one patients were enrolled, including nine patients at 5 mg, six patients at 10 mg, and six patients at 15 mg. One patient at each dose level experienced DLT (acute myocardial infarction, hyperbilirubinaemia and elevated aspartate aminotransferase (AST) at 5‐, 10‐ and 15‐mg, respectively). The calculated MTD of idarubicin was 10 mg. The most frequent grade ≥3 adverse events were pain, elevated AST, elevated γ‐glutamyltranspeptidase and thrombocytopenia. At 2 months, the objective response rate was 52% (complete response, 28%, and partial response, 24%) by modified Response Evaluation Criteria in Solid Tumours. The median time to progression was 12.1 months (95% CI 7.4 months – not reached); the median overall survival was 24.5 months (95% CI 14.7 months – not reached). Pharmacokinetic analysis demonstrated the ability of DEBs to release idarubicin slowly. Conclusions Using drug‐eluting beads, the maximum‐tolerated dose of idarubicin was 10 mg per TACE session. Encouraging responses and median time to progression were observed. Further clinical investigations are warranted (NCT01040559).